Exploring the hidden influence of international treaty secretariats: using social network analysis to analyse the Twitter debate on the ‘Lima Work Programme on Gender’ - Jörgens, H.; Kolleck, N.; Saerbeck, B. (Journal of European Public Policy, 2016)
While there is little doubt that international public administrations (IPAs) exert autonomous influence on international policy outputs, scholars struggle with the problem of how to measure this influence. Established methods for assessing political influence are of limited use when focusing on international bureaucracies. The main reason is that IPAs do not explicitly state their policy preferences. Instead, they tend to present themselves as neutral administrators, aiming to facilitate intergovernmental agreement. They normally act ‘behind the scenes’. We propose social network analysis (SNA) as an alternative method for assessing the hidden influence of international treaty secretariats. SNA infers influence from an actor’s relative position in issue-specific communication networks. We illustrate the application and usefulness of this method in a case study on the role of the United Nations climate secretariat in a policy-oriented Twitter debate on incorporating gender issues into the global climate policy regime.